Effect of GLP-1 Receptor Agonists (Liraglutide) on Glycemic Parameters and Circulating miRNA Expression in Type 2 Diabetes Mellitus - Aqeel Meer AL-ZAMILY (Modern Medicine)
Background: Circulating miRNA modulates a variety of cellular activities including the pathogenesis of many diseases. In type 2 diabetes mellitus (T2DM), alteration in miRNA profiles can have a significant effect on insulin signaling, β-cell function, and inflammation. It has been suggested that antidiabetic therapies can normalize circulating miRNA levels and improve metabolic parameters, rendering miRNA as potential biomarkers for T2DM monitoring and treatment response. Aim: To examine the impact of GLP-1 receptor agonists on the glycemic profile and on circulating levels of miRNA-146a, miRNA-21, and miRNA-222. Materials and methods: The study included 60 patients who were recently diagnosed with T2DM. Pre-treatment levels of glycemic parameters (HbA1c and FPG) were quantified with specific diagnostic kits on the Cobas-4000 the clinical chemistry analyzer. Pre-treatment levels of circulating miRNA levels (miRNA-146a, miRNA-21, and miRNA-222) were assessed using a two-step quantitative RT-PCR assay on a 96–well plate after a total RNA isolation and quantification. Patients were then prescribed subcutaneous liraglutide at 1.5 mg/day for six months, then post-treatment levels of HbA1c, FPG, and miRNAs were assessed again and compared with pre-treatment findings to evaluate changes in glycemic parameters and circulating miRNA levels. Results: Liraglutide significantly reduced HbA1c (from 7.89 ± 0.57% to 5.72 ± 0.43, p = 0.015) and FPG (from 157.66 ± 9.98 mg/dL to 113.51 ± 15.25 mg/dL, p < 0.001), and decreased BMI (p = 0.046). miRNA-146a and miRNA-222 levels were significantly upregulated, while miRNA-21 was downregulated following treatment (p < 0.001 for all). miRNA-146a and miRNA-222 negatively correlated with HbA1c and FPG, whereas miRNA-21 showed a positive correlation. ROC analysis showed strong diagnostic performance for miRNA-146a (AUC = 0.869) and miRNA-222 (AUC = 0.816), with moderate predictive value for miRNA-21 (AUC = 0.709). Conclusion: Liraglutide displayed significant glycemic control in patients with T2DM. Liraglutide also significantly alters circulating miRNA profiles. The regulation of miRNA-146a, miRNA-21, and miRNA-222 highlights the potential application of these miRNAs as biomarkers for treatment monitoring and suggests a role in the therapeutic mechanisms of GLP-1 receptor agonists.